AUTOIMMUNE HEMOLITYC ANEMIA IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA: SINGLE CENTER EXPERIENCE - Trajkova, Sanja; Krstevska-Balkanov, Svetlana; Pivkova-Veljanovska, Aleksandra; Stojanovski, Zlate; Popova-Labacevska, Marija; Ridova, Nevenka; Stojanovska-Jakimovska, Simona; Cvetanovski, Milce; Risteska, Tara; Kocoski, Bozidar; Fazliu, Arita; Panovska-Stavridis, Irina (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Autoimmune phenomena are a well-known complication of lymphoproliferative diseases, particular in chronic lymphocytic leukemia (CLL). Autoimmune hemolytic anemia(AIHA) is the most frequent autoimmune disorder described in CLL. AIHA is more frequently found in patients with unfavorable biological risk factors for CLL.   Aim of the study: Evaluation of AIHA in chronic lymphocytic leukemia patients from Republic of North Macedonia in correlation with genetic structure of pathologic B lymphocyte. Material and methods: This is a retrospective study of 100 patients with CLL, diagnosed and followed in the period between January 2012 and January 2022. Traditional laboratory, clinical prognostic, and biological prognostic factors were evaluated at first patient visit to University Clinic of Hematology -Skopje Macedonia. Immunohematology workup was performed Institute for Transfusion, Skopje, North Macedonia.  Mutational status and configuration of IGHV-IGHD-IGHJ rearrangements and genetics were analyzed using reverse transcriptaseâ€“ polymerase chain reaction (RT-PCR) and sequencing methodology. Results: A diagnosis of AIHA was made in 10% of the new diagnosed treatment naÃ¯ve CLL patients observed at our institution. Seventy percent of the patients have unmutated IGHV gene. The genetic results presented most frequent unfavorable cytogenetics with 11q deletions and NOTHCH mutation. TTF was 11,3 months and OS of CLL/AIHA was 35,9months. Conclusion: This study indicates that AIHA is a rare event in CLL with a significantly higher incidence in patients with   unmuteted  IGHV genes  subgroup IGHV1-69 and adverse genetic profile with 11q deletions  and NOTHCH mutation. The results of our study are consistent with published studies with specific molecular signature.  Keywords: CLL, AIHA, unmutated IGHV, del11q.